2016
DOI: 10.1530/eje-15-0922
|View full text |Cite
|
Sign up to set email alerts
|

Growth patterns of patients with Noonan syndrome: correlation with age and genotype

Abstract: Background: Growth patterns of patients with Noonan syndrome (NS) were established before the involved genes were identified. Objective: The goal of this study was to compare growth parameters according to genotype in patients with NS. Subjects and methods: The study population included 420 patients (176 females and 244 males) harboring mutations in the PTPN11, SOS1, RAF1, or KRAS genes. NS-associated PTPN11 mutations (NS-PTPN11) and NS with multiple lentiginesassociated PTPN11 mutations (NSML-PTPN11) were dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 36 publications
11
47
0
Order By: Relevance
“…It has been suggested that the association between body fat and age of pubertal onset in boys may be nonlinear with delayed puberty seen in very lean as well as in very obese boys (25). As previously reported in NS (19,29,30), our patients displayed a lean phenotype with a BMI in the lower normal range which may influence the timing of puberty. The relationship between fat mass and puberty may be mediated by several factors, including leptin, the levels of which are very low in our patients.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…It has been suggested that the association between body fat and age of pubertal onset in boys may be nonlinear with delayed puberty seen in very lean as well as in very obese boys (25). As previously reported in NS (19,29,30), our patients displayed a lean phenotype with a BMI in the lower normal range which may influence the timing of puberty. The relationship between fat mass and puberty may be mediated by several factors, including leptin, the levels of which are very low in our patients.…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, Sertoli cell markers levels significantly varied according to the genotype with lower levels in NS-PTPN11 and RAF1 patients than in SOS1 patients. Of note, the same impact of genes was found for growth impairment, infants with SOS1 mutations being less short than those with NS-PTPN11 or RAF1 mutations (19). These differences between genotypes may be explained by variations in the degree of activation of the RAS/ERK signalling pathway or by differential, genotype-dependent, tissue specificity.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…gressive growth failure in infancy, sustained growth in childhood (below -2 standard deviation scores [SDS] of the growth curve of normal children), delayed growth spurt in puberty, and short stature in adulthood (just below -2 SDS) [1,[6][7][8][9].…”
mentioning
confidence: 99%
“…Currently, most phenotypic analyses in RASopathies are based on comparison at the gene level (23)(24)(25)(26), but there is high phenotypic heterogeneity within patients having mutations in the same gene (12). Independent of genetic background, it is important to know whether some mutations can cause more severe phenotypes than others.…”
mentioning
confidence: 99%